2001
DOI: 10.1182/blood.v97.7.2053
|View full text |Cite
|
Sign up to set email alerts
|

Identification of polymorphisms in the promoter and the 3′ region of the TAFI gene: evidence that plasma TAFI antigen levels are strongly genetically controlled

Abstract: Thrombin-activable fibrinolysis inhibitor (TAFI) is a recently described carboxypeptidase that is potentially involved in the regulation of fibrinolysis by decreasing plasminogen binding to the fibrin surface. This role makes the TAFI gene a good candidate in atherothrombotic diseases. The great interindividual variability of plasma TAFI antigen levels is poorly explained by lifestyle characteristics, thus suggesting its genetic determination. To test this hypothesis, the promoter and the 3-untranslated region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
156
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(178 citation statements)
references
References 14 publications
17
156
0
5
Order By: Relevance
“…between individuals and therefore have been believed to be mainly regulated by genotype (17). The mechanism underlying association between elevated plasma TAFI and LDL cholesterol in type 2 diabetic patients remains to be determined.…”
Section: Pai-1 and Tafi In Diabetes With Msmentioning
confidence: 99%
See 1 more Smart Citation
“…between individuals and therefore have been believed to be mainly regulated by genotype (17). The mechanism underlying association between elevated plasma TAFI and LDL cholesterol in type 2 diabetic patients remains to be determined.…”
Section: Pai-1 and Tafi In Diabetes With Msmentioning
confidence: 99%
“…PAI is produced mainly by adipose tissues and vascular endothelial cells (21), while TAFI is produced exclusively by the liver (14). Another possibility is that plasma TAFI concentrations may be regulated more strongly by genotype rather than metabolic factors as mentioned above (17).…”
Section: Pai-1 and Tafi In Diabetes With Msmentioning
confidence: 99%
“…These polymorphisms are in strong linkage disequilibrium and form 4 main haplotypes. 78 In a multivariate analysis, the Ala147Thr and 1542C/G polymorphisms in combination showed the strongest influence (Ͼ60%) on TAFI level variability; however, the mechanism for this effect is not yet understood. In fact, a recent segregation-linkage analysis suggested that these polymorphisms were only markers in linkage disequilibrium with unidentified TAFI-linked quantitative trait loci.…”
Section: Thrombin-activatable Fibrinolysis Inhibitormentioning
confidence: 99%
“…Thrombin activatable fibrinolysis inhibitor levels are also genetically determined and the )438 G/A TAFI single nucleotide polymorphism (SNP) in the promoter region (Henry et al, 2001) and the 505 G/A SNP (Henry et al, 2001) and 1040 C/T SNP in the coding region (Brouwers et al, 2001) are associated with TAFI plasma antigen levels. The )438 G/A polymorphism was reported to be associated with an increased risk of developing venous thrombosis (Franco et al, 2001;Zidane et al, 2003).…”
mentioning
confidence: 99%